KONTRIBUSI KETERAMPILAN MENYIMAK PANTUN TERHADAP KETERAMPILAN MENULIS PANTUN SISWA KELAS VII SMP NEGERI 34 PADANG - Syafitri, Rahmida; Zulfikarni, Zulfikarni (Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2019)
ABSTRACT This article is written to discuss the results of research on contribution of skills listening rhyme to writing skills rhyme grade strudents VII SMP Negeri 34 Padang.  The purpose of this research there are three. First, describe the skills of listening rhyme. Second, describe the skils of writing rhyme. Third, describe the contributing skills of listening rhyme for the writing skill of the rhyme grade students VII SMP Negeri 34 Padang. This research type is quantitative descriptive method. The design used in this research is the design contribution. This research population is grade VII SMP Negeri 34 Padang are registered on the school year 2018/2019, i.e. as many as 277 students. The sample in this research are determined by proportional random sampling of 15% of the population, i.e. 45 students. Research data is a score test results intermediate listening rhyme and score the writing skills test result text rhyme. The data obtained through two types of tests i.e. objective tests to measure the skills of listening rhyme and performance tests to measure the skills of writing a text rhyme. The results of the research there are three. First, the skills of listening rhyme grade VII SMP Negeri 34 Padang are on good qualifications (B) by the value of the average 77,67. Second, the skills of writing rhyme grade VII SMP Negeri 34 Padang are on good qualifications (B) with an average of 82,31. Third, there is a contribution of listening skills rhyme to the skills of writing rhyme of class grade VII SMP Negeri 34 Padang at 57,15% Kata kunci: Kontribusi, Menyimak, Menulis, dan Pantun